Applications of saturation transfer difference NMR in biological systems - Bhunia, Anirban (2013)
The method of saturation transfer difference (STD) nuclear magnetic resonance (NMR) is an indispensable NMR tool in drug discovery. It identifies binding epitope(s) at the atomic resolution of small molecule ligands (e.g. organic drugs, peptides and oligosaccharides), while interacting with their receptors, such as proteins and/or nucleic acids. The method is widely used to screen active drug molecules, simultaneously ranking them in a qualitative way. STD NMR is highly successful for a variety of high molecular weight systems, such as whole viruses, platelets, intact cells, lipopolysaccharide micelles, membrane proteins, recombinant proteins and dispersion pigments. Modifications of STD pulse programs using 13C and 15N nuclei are now used to overcome the signal overlapping that occurs with more complex structures.